(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article examines the application of artificial intelligence (AI) in the automation of machine-building production. The article describes the main tasks that can be solved with the help of AI, such as production optimization, quality control, prediction of equipment failures, etc. Examples of successful AI implementation in mechanical engineering are given, such as the use of neural networks to predict equipment failures, automatic recognition of defects on the surface of parts, etc.